Mini Review: Socio-Cultural Influences on the Link Between ADHD and SUD - Slobodin, Ortal; Crunelle, Cleo L. (Frontiers in Public Health, 2019)
The prevalence of Attention-deﬁcit/hyperactivity disorder (ADHD) in patients with substance use disorders (SUD) varies across countries and cultures. So far, cross-cultural variance in ADHD prevalence rates among SUD patients was mainly ascribed to different types of abused substances and their availability, the setting (e.g., outpatient versus inpatient), different sample sizes, and the diagnostic procedure (e.g., screening questionnaire versus structured clinical interview). However, most of these studies focused on characteristics intrinsic to ADHD (e.g., impulsivity, novelty seeking, disinhibition) as risk factors for SUD, leaving the role of societal and cultural practices in the ADHD-SUD link hardly acknowledged. The aim of the present mini-review is to address this gap in the literature by providing evidence for the effect of socio-cultural practices on the ADHD-SUD link and suggesting directions for future research. To achieve this goal, we map the influence of socio-cultural factors on the ADHD-SUD link along three lines of research. The first line is concerned with the role of socio-cultural factors in the recognition, diagnosis, and treatment of childhood ADHD. The second line of research is concerned with socio-cultural influences on substance use (e.g., religion, ethnic identity, acculturation, and socioeconomic status). Finally, we describe potential socio-cultural factors which may operate as mechanisms for reducing or increasing access to substance abuse treatment (e.g., ethnic disparities in health care utilization). Identifying socio-cultural influences on the ADHD-SUD link may provide further insight into the bidirectional association between ADHD and SUD in different contexts and encourage future research in the field.